2004
DOI: 10.1128/jcm.42.12.5917-5920.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Analysis of Escherichia coli Isolates Producing Extended-Spectrum β-Lactamases for Identification of Nosocomial Outbreaks in Stockholm, Sweden

Abstract: From June to October of 2002, a cluster of Escherichia coli isolates producing extended-spectrum β-lactamases (ESBLs) was detected in Stockholm. The isolates were grouped into two clones, one of which had already circulated in the same area before the outbreak. CTX-M-type ESBLs and coresistance to ciprofloxacin were identified in the strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…Thus, this endemic strain might have undergone genetic alterations over time and site. Clone 1 was also one of the clones involved in the first ESBL outbreak reported in Sweden 2002 (8). Clone 2 was another clone involved in the outbreak 2002; however, no more such strains were recovered after the outbreak during this study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this endemic strain might have undergone genetic alterations over time and site. Clone 1 was also one of the clones involved in the first ESBL outbreak reported in Sweden 2002 (8). Clone 2 was another clone involved in the outbreak 2002; however, no more such strains were recovered after the outbreak during this study period.…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were screened for the resistance genes SHV, TEM, CTX-M, and OXA by a multiplex PCR assay using universal primers (Table 1) (3,8,12,15). Bacterial DNA extraction was performed in a MagNA Pure LC System (Roche Diagnostics GmbH, Mannheim, Germany) by using a MagNA Pure LC DNA isolation kit I. PCR amplification reactions were performed in a volume of 25 l containing 12.5 l of 2ϫ Qiagen Multiplex PCR Master Mix (Qiagen GmbH, Hilden, Germany), 0.2 M concentrations of each primer, and 2 l of DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…A worldwide distribution of these enzymes has been reported (4), and in some settings (e.g., Argentina, Greece, Japan, Spain, and Taiwan), the CTX-M-type enzymes are more prevalent than TEM-and SHV-type ESBLs (35,36,43,45,46). In Europe, where the TEM-and SHV-type ESBLs were first reported (20,40) and are widespread overall (12,26,30,33,37), a rapid and massive dissemination of isolates producing CTX-M-type ESBLs has recently been reported in some countries (1,16,17,21,25,44) and is a matter of major concern.…”
mentioning
confidence: 99%
“…One of these enzymes, CTX-M-15, is now found worldwide, mainly in Escherichia coli isolates recovered in hospitals and in the community and responsible for outbreaks in France, the United Kingdom, Sweden, and Canada (11,12,25,28,29,30,33,40). Molecular characterization of plasmids encoding CTX-M-15 from E. coli strains involved in outbreaks in different countries showed that they additionally carried other antibiotic resistance genes, such as bla OXA-1 , bla TEM-1 , tetA, aac(6Ј)-Ib, and aac(3)-II, and sometimes a class 1 integron (6,23,27).…”
mentioning
confidence: 99%